2014
DOI: 10.1083/jcb.201402006
|View full text |Cite
|
Sign up to set email alerts
|

Prestress in the extracellular matrix sensitizes latent TGF-β1 for activation

Abstract: A mild strain induced by matrix remodeling mechanically primes latent TGF-β1 for its subsequent activation and release in response to contractile forces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(165 citation statements)
references
References 74 publications
5
156
0
4
Order By: Relevance
“…αvβ8 on lung fibroblasts has been suggested to take part in lung fibrosis, via a mechanism involving TGF-β activation by myofibroblasts [58]. Hinz has recently elegantly demonstrated that stiffness of the ECM can sensitize TGF-β to activation [59]. The importance of β1 integrin function for TGF-β signaling was also underlined by the phenotype of mice lacking the β1 integrin associated protein integrin-linked kinase (ILK) in fibroblasts [60].…”
Section: Tgf-β Activating Integrinsmentioning
confidence: 86%
“…αvβ8 on lung fibroblasts has been suggested to take part in lung fibrosis, via a mechanism involving TGF-β activation by myofibroblasts [58]. Hinz has recently elegantly demonstrated that stiffness of the ECM can sensitize TGF-β to activation [59]. The importance of β1 integrin function for TGF-β signaling was also underlined by the phenotype of mice lacking the β1 integrin associated protein integrin-linked kinase (ILK) in fibroblasts [60].…”
Section: Tgf-β Activating Integrinsmentioning
confidence: 86%
“…It is regulated by a variety of mechanisms including ligand processing, phosphorylation, and inhibitory Smad proteins (Massague, 2012). ECM mechanical remodeling has been shown to regulate TGF‐β1 activation by releasing TGF‐β1 from the ECM microenvironment (Wells & Discher, 2008; Klingberg et al ., 2014). Our findings demonstrate another level of regulation of TGF‐β by mechanical force; reduced mechanical force can down‐regulate the ability of cells to respond to TGF‐β via specific down‐regulation of TβRII.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired VSMC differentiation in Mmp17 −/− mice could also be related to the altered ECM organization, which might directly decrease Tgfb1 availability. 33 Proteome analysis did not reveal changes in the levels of the contractile proteins smooth muscle myosin heavy chain or calponin but did indicate an important contribution to the phenotype from alterations to actomyosin and cell-adhesion pathways likely related to matrix/force-dependent responses. Proteomics analysis also identified mitochondrial dysfunction in the dedifferentiated phenotype of Mmp17-null aortic VSMCs, both in neonates and adults.…”
Section: Discussionmentioning
confidence: 99%